Pelatihan Kewirausahaan Pada Masa Pandemi Covid-19 Kepada Siswa-Siswi SMK Nurul Hikmah Langko Kabupaten Lombok Barat - Handry Sudiartha Athar; Muhammad Sarjan; Lalu Hamdani Husnan (Pascasarjana Universitas Mataram, 2021)
The impact of Covid-19 not only occurs on health aspects, but penetrates in the world of education. This devotional activity aims to empower the entrepreneurial spirit through entrepreneurship training activities as a means of fostering an entrepreneurial spirit so that students can be independent after completing their education. This method of community service is done by means of varied lectures, demonstrations, and exercises. The results of this activity can be concluded that there is an increase in information from students about entrepreneurship. Students have a more understanding related to the importance of having an entrepreneurial spirit so that students can be independent after completing their education